Team-building with teachers - Chivers, Judith (London : Kogan page limited, 1995)
One of the many results of changes in education since the 1980s is an increased emphasis on effective teamwork. Drawing on her experience in training and consultancy work in schools, the author here offers practical approaches for successful team-building.
Includes bibliographical.
Keywords: Teachers -- In service-training -- United States; Teaching teams -- United States; Team learning approach in education -- United States